Analisis Status Hidrasi dan Asupan Zat Gizi Serta Air pada Ibu Hamil - Mulyani, Erry Yudhya; Hardinsyah, Hardinsyah; Briawan, Dodik; Santoso, Budi Iman (Media Kesehatan Masyarakat Indonesia, 2018)
Pregnancy is a specific physiological period, which is the nutritional requirements increase more than those of normal condition. About 50-70% of pregnant women experience nausea and vomiting, it was affects to the lack of nutrient intake for mothers and infants. The sustainability of mother’s condition can cause an imbalance of body fluid which has impact on the mother’s hydration status. The aims of this study were to analyze the relationship between characteristics, socio-economic, nutritional status, nutritional intake and water with hydration status. This study was a cross sectional study, conducted on the area of primary of public health at Kebon Jeruk Regency, West Jakarta. The subject were pregnant women who in the second trimester, examined pregnancy in the study area amounted to 107 subjects. Independent t-test and chi-square test were used to analyzed the data. Subjects were divided into two groups based on hydration status from urin osmolality concentration; normal and hypohydrated. The average of urine osmolality in the hypohydration group and normal, were 838.78±172.35 mOsm/Kg and 268.05±116.64 mOsm/Kg, respectively. Subject’s characteristics (age, gestational age, body weight, height, nutritional status before pregnancy, upper arm circumference, waist circumference, hip circumference, blood pressure) did not differ between two groups (p≥0.05). There were no relationship between edu- cation of mothers and fathers, employment status of mothers and fathers, household expenditure, and mother’s know-ledge (p≥0.05). There were differences of energy, carbohydrate and zinc intake between two groups (p<0.05), but didn’t found differences intake of (protein, fat, calcium, iron, folic acid) and water between two groups (p≥0.05). However, the mother should more attention to fulfil their nutrients and water intakes to support the foetus growth.